A Case of Severe Heatstroke and Review of Pathophysiology, Clinical Presentation, and Treatment. (November 2013) - Horseman, Michael A.; Rather-Conally, Jacquelyn; Saavedra, Crystal; Surani, Salim
Heatstroke is life-threatening condition characterized by hyperthermia and central nervous system disturbances. It can also be classified as a form of systemic inflammatory response syndrome with multiple organ dysfunction and in many ways resembles sepsis. Like sepsis, most patients with heatstroke demonstrate a hyperdynamic hemodynamic response. In contrast to sepsis, rhabdomyolysis may complicate management and initial fluid resuscitation is not well defined. We present an illustrative case report and review of literature.